Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1097/rct.0000000000000863
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Magnetic Resonance Provides Evidence of Abnormal Myocardial Strain and Primary Cardiomyopathy in Marfan syndrome

Abstract: Objective Marfan syndrome is an autosomal-dominant genetic disorder caused by mutations in the fibrillin-1 gene. The condition is a connective tissue disease that frequently involves the cardiovascular system. The existence of a primary cardiomyopathy in Marfan syndrome, however, is controversial. The aims of this study were to investigate the prevalence of left ventricular dysfunction with both transthoracic echocardiography and cardiovascular magnetic resonance (CMR) in a cohort of Marfan syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…No association was found between reduced LV EF and age, gender, indexed aortic dimensions, presence of mitral valve prolapse or valve regurgitation, providing additional evidence that the impairment in ventricular function is inherent to the underlying connective tissue abnormality in MFS. Similar findings were observed in the CMR studies by de Witte et al and by Winther et al, confirming that the reduced LV EF, is mostly mild but might affect a subgroup of patients in a more severe way [ 29 , 30 ]. By extending the detection prowess of conventional echocardiography, studies utilizing strain and strain rate imaging to assess and quantify changes in global and regional contractile function have confirmed the findings obtained from CMR [ 30 , 31 , 32 , 33 ].…”
Section: Myocardial Involvementsupporting
confidence: 86%
See 1 more Smart Citation
“…No association was found between reduced LV EF and age, gender, indexed aortic dimensions, presence of mitral valve prolapse or valve regurgitation, providing additional evidence that the impairment in ventricular function is inherent to the underlying connective tissue abnormality in MFS. Similar findings were observed in the CMR studies by de Witte et al and by Winther et al, confirming that the reduced LV EF, is mostly mild but might affect a subgroup of patients in a more severe way [ 29 , 30 ]. By extending the detection prowess of conventional echocardiography, studies utilizing strain and strain rate imaging to assess and quantify changes in global and regional contractile function have confirmed the findings obtained from CMR [ 30 , 31 , 32 , 33 ].…”
Section: Myocardial Involvementsupporting
confidence: 86%
“…Three subsequent studies using CMR provided additional evidence for myocardial involvement, as demonstrated by the observation of a reduced LV EF in a subgroup of patients [ 28 , 29 , 30 ]. In 2010, Alpendurada et al evaluated 68 patients with MFS without significant valvular disease or prior cardiovascular surgery [ 28 ].…”
Section: Myocardial Involvementmentioning
confidence: 99%
“…Angtuaco et al did not observe any significant differences in LV longitudinal, radial and circumferential strain in a small cohort of paediatric MFS patients (N = 16) compared to controls, but detected reduced regional strain rates, suggesting that the study might be underpowered [34]. To date, there is only one retrospective CMR study by Winther et al that used featuretracking CMR to characterise adult MFS patients, demonstrating a reduced LV longitudinal strain pattern in some patients [9]. However, the authors could not report on LV circumferential strain due to lacking short-axis cine stack in their CMR protocol [9].…”
Section: Strain Analysis In Patients With Mfsmentioning
confidence: 97%
“…The well-known cardiovascular manifestations are aortic dilatation and dissection, and heart failure caused by aortic or mitral valve regurgitation [2,4]. However, there are studies suggesting the existence of cardiac dysfunction in the absence of valvular disease [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…These patients can also have subclinical signs of ventricular dysfunction even with preserved left ventricular ejection fraction (LVEF) [26]. Strain analysis can help identify early regional dysfunction [29] (Fig. 2).…”
Section: Cmr In Muscular Dystrophymentioning
confidence: 99%